Comprehensive analysis of the bridge between strategic planning & operational execution of Asiatic Experiential Marketing Ltd. - Trina, Jarin Tasnim (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.